Análise da eficácia do programa Vida no Trânsito no combate à violência viária em Palmas/TO, no período entre 2011 e 2018 - Ferreira, Junia (Universidade Federal do Tocantins, 2021)
Analysis of the effectiveness of the Life in Traffic Program (PVT) in combating road violence in the Municipality of Palmas, capital of the State of Tocantins, between the years 2011 to 2018. The program is an international initiative whose methodology was initially applied in ten countries of the world, including Brazil, and focuses on standardizing information on serious and fatal traffic accidents to enable public managers to design and apply strategies to reduce traffic morbidity and mortality. Palmas was one of the five Brazilian capitals selected for the development of the PVT from 2011 and continues its application to the present day. It is a capital of only 31 years old, however, it already suffers from common problems in old cities, such as real estate speculation, deficient transport system and disorderly expansion - factors that correlate with the theme of road insecurity and consequent reduction in the quality of life of the city. population. In addition to the necessary bibliographic review, in order to carry out the proposed analysis, documental and field research were used as methodology, the first of which was more quantitative and the second, qualitative. As a result, the contribution and validity of the PVT is demonstrated, as well as the need for this public policy to be taken more seriously by its executors in order to consolidate itself in the municipality with the desired efficiency.